Why neurology? Factors which influence career choice in neurology. (2nd January 2016) - Albert, Dara V.; Hoyle, Chad; Yin, Han; McCoyd, Matthew; Lukas, Rimas V.
Abstract : Objective: To evaluate the factors which influence the decision to pursue a career in neurology. Methods: An anonymous survey was developed using a Likert scale to rate responses. The survey was sent to adult and child neurology faculty, residents and fellows, as well as medical students applying for neurology. Descriptive statistics were used to analyse the factors of influence. Respondents were subsequently categorized into pre-neurology trainees, neurology trainees, child neurologists and adult neurologists, and differences between the groups were analysed using Pearson's chi-square test. Results: One hundred and thirty-three anonymous responses were received. The respondents were neurologists across all levels of training and practice. Across all respondents, the most common factor of high importance was intellectual content of specialty, challenging diagnostic problems, type of patient encountered and interest in helping people . Responses were similar across the groups; however, the earliest trainees cited interest in helping people as most important, while those in neurology training and beyond cite intellectual content of the specialty as most important. Discussion: As trainees transition from their earliest levels of clinical experience into working as residents and faculty, there is a shift in the cited important factors. Lifestyle and financial factors seem to be the least motivating across all groups. Encouragement from peers, mentors, faculty and practicing physicians is considered high influences in a smaller number of neurologists. This may present an opportunity for practicing neurologists to make connections with medical students early in their education in an effort to encourage and mentor candidates.